Survivorship of the retained femoral component after revision total hip arthroplasty: A systematic review and meta-analysis - Li, Hua; Zhuang, Tengfeng; Wu, Wenrui; Gan, Wenyi; Wu, Chongjie; Peng, Sijun; Huan, Songwei; Liu, Ning (Frontiers in Surgery, 2022)
Objective This systematic review and meta-analysis aimed to estimate re-revision rates of retained femoral components after revision total hip arthroplasty (THA). Methods Papers were searched in the PubMed, Embase, Web of Science and Cochrane Library databases with predetermined keywords from January 2000 to January 2022. The studies reporting the re-revision rates of retained stems after revision THA were identified. Pooled rates of re-revision for any reason and aseptic loosening were calculated using a random-effects model or a fixed-effects model based on the results of heterogeneity assessment after the Freeman-Tukey double-arcsine transformation. A meta-regression was performed to explore potential sources of heterogeneity. Results There were 20 studies with 1484 hips that received the isolated cup revision with the femoral component retained. The pooled re-revision rate of retained stems was 1.75% (95% confidence interval [CI] 0.43%, 3.65%). The re-revision rate of retained stems due to aseptic loosening was 0.62% (95% CI 0.06%, 1.55%). The meta-regression showed that the fixation type (cemented or cementless) was related to the re-revision rate for any reason and the re-revision rate for aseptic loosening. Conclusion Based on the existing evidence, the isolated cup revision with a stable stem in situ yields low re-revision rates. The cement status of retained stems may influence the survivorship of stems.